Developmental enamel defects in tuberous sclerosis: a clinical genetic marker?. Issue 8 (August 1997) - Flanagan, N; O'Connor, W J; McCartan, B; Miller, S; McMenamin, J; Watson, R
Abstract : Ten probands with tuberous sclerosis (TS) and 20 first degree relatives were examined for evidence of pitted enamel hypoplasia; 100% of TS patients had pitting, compared to 65% of relatives and 72% of 25 controls. We found that 70% of TS cases had more than 14 pits per person compared with only 5% of relatives and 4% of controls; 85% of relatives and 84% of controls had fewer than six pits per person. Our results confirm that significantly increased numbers of dental enamel pits are found in persons with TS compared to controls. These results suggest that examination for the presence or absence of dental enamel pits is not a useful screening test for first degree relatives to detect otherwise unsuspected subjects with tuberous sclerosis. However, the lack of pits in first degree relatives in our study is probably largely because none of the relatives appeared to carry the TS gene.